Evaluating Grease Degradation through Contact Angle Approach - Michael M. Khonsari; K. P. Lijesh; Roger A. Miller; Raj Shah (Lubricants, 2021)
Grease is highly susceptible to degradation due to regular usage and the severity of the operating conditions. Degradation can negatively impact the performance of grease-lubricated machinery, demanding frequent maintenance to avoid premature failure of machine elements. Quantification of grease degradation has proven to be a formidable task, for which no accepted standards are currently available. In this paper, we extend the results of a novel approach developed recently for the evaluation of the water-resistant property in grease to quantify degradation. The methodology is based on measurements of the contact angle of a water droplet on the surface of a sample of grease. We report the results of extensive tests performed on different grades of lithium complex greases to evaluate the variation of contact angle values with the composition of grease. The measurements were compared with penetrometer readings to quantify a relationship between the grease consistency and contact angle. Detailed study results are also presented on three types of greases sheared in a grease worker for a different number of strokes: contact angle and the yield stress values were measured and compared. Finally, the tribological characteristics were determined for two greases that exhibited a low or high change in their contact angles.